Public Health Evaluation:Avoidance of Breast Cancer Screening in Immigrant Canadians - Maisha, Marjana; Begum, Monirun; Yasmeen, B H Nazma (Northern International Medical College Journal, 2024)
Breast cancer is one of the leading causes of death in Canadian women.1This cancer can be detected early through screening and allow for higher chances of survival. However, the Canadian Cancer Statistics Advisory Committee found that it is still being diagnosed at late stages, even with organized screening programs implemented in Canadian provinces.1 In Ontario, mammography is recommended every two years for women ages 50-69 years where they receive a medical referral letter invitation, but women are still found to present in clinics with no history of screening or advanced cancer.2 In 2017, 26500 breast cancer cases were found and in that 5000 women did not survive, with a majority of these women being immigrant. Canada is a multicultural country where more than 20% of the populations are immigrants, but yet more immigrant women die from breast cancer than non-immigrant women.3,4 However, screening participation rates remain lower in immigrants than non-immigrants,5 possibly being fatal. It’s important to know the causes of screening avoidance. Thus, the purpose of this literature review is to investigate the avoidance of breast cancer screening of immigrant women in Canada. Northern International Medical College Journal Vol. 13 No. 1-2 July 2021-January 2022, Page 566-567